2013
DOI: 10.1002/pon.3288
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study comparing HRQoL among breast, prostate, and colorectal cancer survivors to propensity score matched controls, by cancer type, and gender

Abstract: Background Objectives were to compare health-related quality of life (HRQoL) between breast cancer survivors, prostate cancer survivors (PCS), and colorectal cancer survivors (CCS) to matched controls, stratified by short and long-term survivors, by cancer type, and gender. Methods By using the 2009 Behavioral Risk Factor Surveillance System, propensity scores matched three controls to adult survivors >1 year past diagnosis (N = 11,964) on age, gender, race/ethnicity, income, insurance status, and region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 44 publications
4
32
1
3
Order By: Relevance
“…insomnia) reported by the male group in the three evaluations suggest a coping strategy characterized by introspection and an attempt to mobilize internal resources to solve problems on their own. This response happens especially at the beginning of the treatment when the patient's body is not yet worn out by the chemotherapy's side effects, responding only to the physical symptoms of the disease and to the emotional impact of the diagnosis (Kiss & Meryn, 2001;Krouse et al, 2009;LeMasters, Madhavan, Sambamoorthi, & Kurian, 2013;Nicholas, 2000;Salander & Hamberg, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…insomnia) reported by the male group in the three evaluations suggest a coping strategy characterized by introspection and an attempt to mobilize internal resources to solve problems on their own. This response happens especially at the beginning of the treatment when the patient's body is not yet worn out by the chemotherapy's side effects, responding only to the physical symptoms of the disease and to the emotional impact of the diagnosis (Kiss & Meryn, 2001;Krouse et al, 2009;LeMasters, Madhavan, Sambamoorthi, & Kurian, 2013;Nicholas, 2000;Salander & Hamberg, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, researching different tumour groups is advisable as patients' experiences differ for different types of cancer (LeMasters et al, 2013), but results concerning patients with breast and colorectal cancer are particularly important considering their high incidence rates (Westlake and Cooper, 2008). Finally, interventions based on aforementioned suggestions should be verified in the future to optimise patient care.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…On the one hand, this is reasonable as women typically report more anxiety problems (McLean & Anderson, 2009), but additionally accounting for male patients in this study allows testing of such gender effects. Beyond this, cancer experiences differ for different types of cancer and therefore it is advisable to research different patient groups (LeMasters, Madhavan, Sambamoorthi, & Kurian, 2013). Finally, considering in particular patients undergoing chemotherapy for an exploration of trait and state anxiety suggested itself as this treatment causes higher anxiety levels than other treatment types (Lim et al, 2011), possibly due to its often distressing and potentially life threatening side effects (Du, Osborne, & Goodwin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This study also found that the evolution of HRQOL scores from the third to the sixth month after experiencing the attack followed a sex-specific pattern: men showed greater improvements in most dimensions of physical and social functioning, while women improved in social functioning and in only few physical dimensions (Dueñas et al 2011). Moreover, female cancer patients (colorectal and breast cancer) have been found to have lower HRQOL levels than their male counterparts (colorectal and prostate cancer) (LeMasters et al 2013). …”
Section: Sex Differences In Health-related Quality Of Lifementioning
confidence: 99%